(untitled) (Journal of the College of Basic Education, 2025)
Rheumatoid arthritis is a chronic autoimmune disease characterized by joint inflammation and damage. Vitamin B12 Plays a vital role in immune function modulation and regulates inflammatory answers. This study aimed to investigated the relationship between vitamin B12 levels and immune markers in patients with rheumatoid arthritis. The study included 50 rheumatoid arthritis patients and 30 healthy controls .A prospective case-control study was conducted in a number of private laboratories and some outpatient clinic for the period between June and September of 2024, involving rheumatoid arthritis patients and healthy controls. The study assessed baseline conditions, randomized patients to receive vitamin B12 supplementation or no intervention, and followed up after 4 weeks. Serum vitamin B12, C-reactive protein, interleukin-6, tumor necrosis factor alpha levels were measured and compared between the two groups. The result of the present study shows that patients with rheumatoid arthritis had significantly lower levels of serum in vitamin B12 compared to the control group. Vitamin B12 was negatively related to the inflammatory markers in patients with rheumatoid arthritis. Taking supplementation with vitamin B12 supplements reduced the levels of inflammatory marker in patients. Conclusion, through the current study shows that adequate levels of vitamin B12 status may help regulate the immune response and alleviate rheumatoid arthritis symptoms by attenuating inflammation. Vitamin B12 could be a potential nutritional intervention for rheumatoid arthritis management.